Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.

The use of near infrared reflectance spectroscopy to study chemical changes in the leaf litter consumed by saprophagous invertebrates (SOIL BIOLOGY & BIOCHEMISTRY, 2001)
Chemical changes in holm oak leaf litter that was consumed by the millipede Glomeris marginata were studied using near infrared reflectance spectroscopy. Compared to leaf litter, faecal pellets were significantly richer in lignin and poorer in nitrogen and readily assimilable constituents. The C:N ratio was significantly higher in the faeces. A NIRS-predicted index of litter decomposability was found to be lower in the faeces than in uneaten litter. (C) 2001 Elsevier Science Ltd. All rights reserved.

Abundance, biomass and functional structure of the saprophagous macrofauna in the litter and soil of Mediterranean oak forests (PEDOBIOLOGIA, 1999)
The saprophagous macrofauna (macroarthropods, gastropods, earthworms) was sampled in five Mediterranean forests of southern France: two helm oak (Quercus ilex) sites on limestone, two downy oak (Q. pubescens) sites on limestone and a helm oak site on schist. The total biomass was high, ranging from 52.1 to 113.1 g fresh mass m(-2). Classification of species into functional groups (epigeic, epi-anecic, anecic and endogeic) showed that the four groups were well represented in this region. However, the density and biomass of epigeic macroarthropods (mainly millipedes) were significantly higher at the helm oak sites on limestone (186 ind. m(-2); 9.6 g m(-2)) than at the other sites. In contrast, the density and biomass of epi-anecic earthworms (Lumbricus spp.) were higher at the downy oak: sites on limestone (13 ind. m(-2); 16.7 g m(-2)). Anecic earthworms (Aporrectodea and Scherotheca spp.) were dominant in terms of biomass at all sites (overall mean 56.6 g m(-2)). Although the results are consistent with possible competitive interactions between epigeic macroarthropods and epi-anecic earthworms, they also show a high degree of coexistence between both of these groups and anecic earthworms. The study provides an insight into the possible responses of the macrofauna of N-W Europe to climate change towards warmer and drier conditions. There is potential for maintenance of all the functional groups that take part in the formation of forest mull.

Belowground biodiversity in a Mediterranean landscape: relationships between saprophagous macroarthropod communities and vegetation structure (Biodiversity and …, 1999)
Millipedes and woodlice were sampled at 27 sites in a mosaic landscape in order to establish the extent to which the macroarthropod community changed with dierent plant for- mations. Multivariate analyses conducted on abundance data for ten species revealed four main types of macroarthropod communities. This classi®cation was highly correlated with vegetation structure and particularly the degree of openness of the sites. Communities dominated by Om- matoiulus rutilans (Julidae) occurred in open grassland; those dominated by Glomeris marginata (Glomeridae) plus Porcellio gallicus (Porcellionidae) were found at the least open sites, with a high oak cover; communities with a high proportion of the endemic glomerid Glomeris annulata oc- curred in semi-open sites with a substantial cover of shrubs. Species diversity was signi®cantly higher at the semi-open sites, this being interpreted as an edge eect. Population density and biomass were lower at wooded sites. In the context of a regional trend towards woodland ex- pansion, the results are discussed from the viewpoint of conserving the pool of millipede and woodlouse species and of maintaining the abundance of saprophagous macroarthropods in the region's ecosystems.

SEASONAL ABUNDANCE OF MILLIPEDES IN A MEDITERRANEAN OAK FOREST (SOUTHERN FRANCE) (ISRAEL JOURNAL OF ZOOLOGY, 1995)
The millipede community of a helm oak forest (Quercus ilex) in southern France was sampled seasonally for 2 yr, at two depths in the forest floor. Despite the strong seasonality of climatic conditions, both recruitment periods and vertical displacements in the soil change markedly according to species; contrasting examples are provided by Glomeris marginata, which breeds in summer and burrows in winter, and by Opisthocheiron elegans, which behaves the opposite way. At the community level, biomass changes significantly between a spring minimum and an autumn maximum. Such a pattern results from the high abundance of G. marginata, a drought-resisting species which grows and reproduces during summer but experiences substantial winter mortality. The seasonal pattern is different in number of individuals due to the minute litter-dweller Polyxenus lagurus, which has a low population density in early autumn. The biomass of macrosaprophagous millipedes on the site (annual mean of 10.5 g live weight m(-2); autumn peak of 14.6 g live weight m(-2)) is much higher than that recorded further north in Europe, and its significance for litter consumption in Mediterranean forest is discussed.